Effect of Giving Polyphytopharmaca on Improvement in The Degree of Asthma Control through Reduction of Eosinophils and Interleukin-13 Uncontrolled Asthma Patients - Aditya Sri Listyoko; Iin Noor Chozin; Susanthy Djajalaksana (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2020)
Backgrounds: Bronchial asthma is a heterogeneous disease characterized with chronic airway inflammation. The level of asthma control is an indicator of asthma management outcomes. It is influenced by a complex immunological mechanism, included the role of IL-13 as a key biomarker of inflammation. We investigate the effect of Poly-Phytopharm (Kleinhovia hospita 100 mg, Curcuma xanthorriza 75 mg, Nigella sativa 100 mg and Ophiocephalus striatus 100 mg) on the level of asthma control tests (ACT) score, blood eosinophils, and serum IL-13 on not fully controlled asthma stable patients. Methods: This study used quasi-experimental pre and post test methods, in 15 stable asthma patients who were not fully controlled at the pulmonary outpatient clinic of Dr. Saiful Anwar General Hospital, Malang. Assessment of ACT score, blood eosinophils, and serum IL-13 are carried out before and after supplementation of Poly-Phytopharm three times a day, two capsules respectively for 12 weeks. The ACT was scored by the investigator by direct questioning of patients, the blood eosinophil was measured with blood analysis, and the IL-13 in serum was detected with qPCR method. Results: There is significant increase of ACT score (18.07±2.57 to 22.06±1.83; P=0.001). In subject with baseline eosinophils ≥300 pg/mL (n=9), there were significant reduction in blood eosinophils (653.15±276.77/µL to 460.66±202.04/µL; P=0.038), and a decrease of serum IL-13 (17.69±9.901 pg/ml to 16.17±12.438 pg/ml; P=0.609). Conclusions: The administration of poly-phytopharm for 12 weeks improves ACT level, decreases blood eosinophils, and decrease serum IL-13 on not fully controlled asthma stable patients. (J Respir Indo. 2020; 40(3): 130-8)